Exploiting Spatio-Temporal Correlation for Reliable Information Transport in WSNs - Faisal Karim Shaikh; Tariq Jameel Khanzada; Nisar Ahmed Memon (Mehran University Research Journal of Engineering and Technology, 2011)
Delivering reliable services in service oriented architectures entails the underlying basis of having communication network models and well structured systems. With the rapid proliferation of ad-hoc mode of communication the reliable delivery of services increasingly encounter new communication and network perturbations. Empirically the core of service delivery in WSNs (Wireless Sensor Networks) is information transport from the sensor nodes to the sink node where the service resides. In this work we provide a reliable information transport for enhanced service delivery by using spatio-temporal correlation in WSN. The classification for different types of information required by the services is also presented. To overcome dynamic network conditions and evolving service requirements an adaptive retransmission mechanism based on spatial correlation is utilized. Simulation results show that the proposed solutions provide service specific reliability and save expensive retransmissions and thus provide energy efficient solution.